2012
DOI: 10.1128/aac.05756-11
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Dihydroartemisinin and Piperaquine in Pregnant and Nonpregnant Women with Uncomplicated Malaria

Abstract: c Pregnant women are particularly vulnerable to malaria. The pharmacokinetic properties of antimalarial drugs are often affected by pregnancy, resulting in lower drug concentrations and a consequently higher risk of treatment failure. The objective of this study was to evaluate the population pharmacokinetic properties of piperaquine and dihydroartemisinin in pregnant and nonpregnant women with uncomplicated malaria. Twenty-four pregnant and 24 matched nonpregnant women on the Thai-Myanmar boarder were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

35
142
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(182 citation statements)
references
References 59 publications
35
142
5
Order By: Relevance
“…Enzyme auto-induction cannot be excluded as an underlying cause to the time-dependent difference in exposure. However, previous detailed PK studies of oral and parenteral administration of ARS have demonstrated a clear malaria effect on the relative bioavailability thought to result from reduced first pass metabolism (40,41). The decreased absorption rate with increasing parasite density was unexpected and opposite to previous observations (39,(42)(43)(44)(45)(46)(47)(48).…”
Section: Population Pharmacokineticscontrasting
confidence: 55%
See 1 more Smart Citation
“…Enzyme auto-induction cannot be excluded as an underlying cause to the time-dependent difference in exposure. However, previous detailed PK studies of oral and parenteral administration of ARS have demonstrated a clear malaria effect on the relative bioavailability thought to result from reduced first pass metabolism (40,41). The decreased absorption rate with increasing parasite density was unexpected and opposite to previous observations (39,(42)(43)(44)(45)(46)(47)(48).…”
Section: Population Pharmacokineticscontrasting
confidence: 55%
“…However, in some reports, peripheral compartment structures have been proposed for DHA. Differences are likely to reflect sampling methodologies and data censoring due to quantification issues (39,40). Malaria infection (measured by the parasite density) had a significant impact on both absorption rate and relative bioavailability of ARS, resulting in increased absorption during the acute malaria infection compared to the convalescent phase.…”
Section: Population Pharmacokineticsmentioning
confidence: 99%
“…In an African pediatric IPT efficacy study of monthly DHA-PQ or SP-PQ (30), incident malaria was lower in the SP-PQ-treated children. There is evidence that the elimination half-life of the pyrimethamine component of SP may be particularly long in pregnancy (19 days versus 10 days in nonpregnant women) (19) which, given that DHA is eliminated within hours of dosing (14,27), might suggest that SP-PQ is a better choice for IPTp than DHA-PQ.…”
mentioning
confidence: 99%
“…A fixed-dose combination is in widespread use for treatment of uncomplicated falciparum and vivax malaria outside pregnancy (25,26). Available pharmacokinetic and efficacy data from Southeast Asia (14,27,28) and Africa (12,13) suggest that DHA-PQ is safe, well tolerated, and efficacious in pregnant women with uncomplicated malaria and that PQ exposure is similar in pregnant and nonpregnant women, even if DHA exposure may be lower in pregnancy.…”
mentioning
confidence: 99%
See 1 more Smart Citation